Photogrametric techniques to health monitoring control of breakwater`s structure using SCILAB - Lemos, Rute (2018)
The need for shelter zones in coastal areas leads to the construction of structures for shore protection such as breakwaters. Its design is mainly made based in semi-empirical formulas [1] [2] [3] and in the experience of the project designer, being the effectiveness of the breakwater carried out through physical modelling. The Harbours and Maritime Structures Division of National Laboratory (NPE, portuguese acronym) for Civil Engineering (LNEC, portuguese acronym) have developed several experiments in bidimensional and tridimensional models. Through this experiments, the stability of the breakwater is tested and the evaluation of damage is made by counting the armor units dislocated (movements or displacements).This damage evaluation is currently done by visual inspection thus being a subjective method where some relevant movements may go unnoticed.